Private Activity in Water and Sewerage Continues to Contract in the First Semester of 2011 - Militaru, Andreea (World Bank, Washington, DC, 2013)
In the first semester of 2011, twelve new water and sewerage projects with private participation reached financial or contractual closure in four lower- and upper-middle income countries. Additionally, a second phase of the divestiture of Aguas Andinas Empresa Metropolitana de Obras de Santiago de Chile (EMOS), took place in Chile bringing total investment commitments (hereafter, investment) in water and sewerage projects amounted to US$1.6 billion a 12 percent increase compared to 2010 first semester levels. The Chilean divestiture, however, accounted for 62 percent of the total investment in 2011 involving investment commitments of US$986 million.